Ecological movement in Baltic republics in the years of perestroika - A. K. Potapov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the history of the environmental movement in the Baltic republics during the first stages of perestroika (1985–1987). The aim of the paper is to analysis of the use of the environmental agenda to develop political national opposition in the Soviet Baltic republics during the years of perestroika. The objectives of the study are to identify the peculiarities of the formation and activities of movements in defence of ecology in the Baltic republics; to identify the main nodes of environmental problems in each Baltic republic (development of phosphorites in Estonia, planning of oil production on the Curonian Spit in Lithuania, construction of Daugavpils hydroelectric power station). As a result, the Baltic intelligentsia who initiated discussion of these problems and managed to organize various protest actions gained some experience in mobilizing the population of the republics, which was then used in the creation of Popular Fronts and movements. They in turn triggered disintegration mechanisms in the USSR in the next stages of perestroika.